(STRONG) RAINBOW CONNECTION NUMBERS ON CORONA PRODUCT OF PATH AND COMPLETE GRAPHS - Sulistyanto, Andry; Halikin, Ikhsanul; Kusbudiono, Kusbudono; Wijaya, Kristiana (Departemen Matematika dan Sains Data FMIPA Universitas Andalas Padang, 2025)
Let G be an edge-colored, where adjacent edges may have the same color. A u-v path in G is a rainbow u-v path if no two edges of u-v path are colored the same. The graph G is called rainbow-connected if G contains a rainbow u-v path for every two vertices u and v of G. A rainbow connection number of rainbow-connected G is the minimum color in G. A rainbow u-v path is called a rainbow u-v geodesic if a rainbow u-v path of length distance from a vertex u to v. A graph G is strongly rainbow-connected if G contains a rainbow u-v geodesic for every two vertices u and v of G. The minimum color of the edges of G such that G is strongly rainbow-connected is the strong rainbow connection number. In this paper, we disccus (strong) rainbow connection number of corona product of path and complete graph.